MODIFIKASI PELAT PENGAKU PADA PROFIL BAJA MENGGUNAKAN METODE ELEMEN HINGGA - Trihantiyana Ananta Jaya; Dedi Imanuel Pau; Yono Putra (SIARTEK - Jurnal Teknik Sipil dan Arsitektur, 2021)
This study aims to analyze the influence of stiffener shape and spacing on the buckling strength and shear capacity of I-beam steel profiles using the Finite Element Method (FEM) with ANSYS software. The variations examined include triangular and convex stiffener shapes, with spacing of 1 meter and ½ meter. The main parameters analyzed are the critical buckling load, web shear strength, and the stress–strain (σ–ε) relationship of each model. The analysis results indicate that the convex stiffener with a ½- meter spacing demonstrates the best performance in resisting buckling and shear forces, achieving the highest critical load of 5630.49 N and a shear capacity of 1,526,140.98 N. Moreover, the configuration with closer stiffener spacing (½ meter) provides a more uniform stress distribution and better-controlled deformation, making it more effective in enhancing the structural stability of the steel beam. This research contributes to the understanding of efficient stiffener design, which can be applied in the planning of safe and economical steel structural elements.